Propofol but not dexmedetomidine produce locomotor sensitization via nitric oxide in rats - Uskur, Tuğçe; Şenöz, Ayşe Özçetin; Çevreli, Burcu; Barlas, Aydın; Uzbay, Tayfun (Psychopharmacology, 2021)
Rationale The abused potential of some anesthetics has been debated. Measurement of locomotor sensitization is a better way to detect the neurobehavioral plasticity of addiction. Objectives The present study aims to explore whether propofol and dexmedetomidine are capable of inducing locomotor sensitization. Methods Male Wistar rats (250–300 g) were the subjects ( n = 8 for each group). Propofol (20 and 40 mg/kg) and dexmedetomidine (2.5–20 μg/kg) or saline were injected to rats intraperitoneally (IP), and their locomotor activities were recorded for 15 min. Consequently, L-NAME (30 and 60 mg/kg)—a nitric oxide (NO) inhibitory agent—was injected to rats 30 min before propofol (40 mg/kg) or saline injections, and the locomotor activity was recorded. The process was carried out for 13 days, with 7 sessions applied every other day. Results Dexmedetomidine did not produce any significant locomotor sensitization. While propofol (20 mg/kg) produced a significant locomotor sensitization in the last treatment session (day 13), at the higher dose, it prompted a significant locomotor sensitization from the 3rd treatment session. L-NAME blocked propofol-induced locomotor hyperactivity and sensitization significantly without producing any noteworthy changes on the locomotor activity during the testing period of 13 days when administered alone. Conclusions Our results suggest that propofol but not dexmedetomidine produced a significant locomotor sensitization via central nitrergic system. Dexmedetomidine may have a lesser psychostimulant type addictive potential than propofol. Sensitization development by propofol implies that this drug might be effective on the neuroadaptive processes associated with a stimulant type of dependence.